Dampak Pengembangan Agribisnis pada Subak terhadap Pendapatan Rumah Tangga Petani (Kasus di Subak Guama, Kecamatan Marga, Kabupaten Tabanan) - Yudiarini, N.; Susrusa, K. Budi; Astiti, NW. Sri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol. 2 - No. 1 - Mei 2014)
Agriculture and rural development in Indonesia seems to be less attention. If the farmer working individual, with a small area and low capital, they are in a weak position. Rice fields in Bali can not be separated from subak who have an exellence management, efficiency in the allocation of natural and human resources. The purpose of this study was to determine the household income of farmers in Subak Guama, find the distribution of income in Subak Guama and the factors that influence household income of farmers in Subak Guama. The population of the study is all the farmer in Subak Guama. Simple random sampling technique, from 86 people were used. Data obtained were tabulated and analyzed by quantitative and qualitative. The result show that the average household income of farmers in Subak Guama Rp 68.972.115,38/year or Rp 5.747.676,28/Month. Per capita income of farmers in Subak Guama Rp14.674.918,17/year. Gini ratio numbers is 0,324, said low lameness, it means there is an equal distribution income of farmers in Subak Guama. Factors affecting farmers' household income simultaneously ie age of farmer, Subak role , social  and economic benefits . Partial factors that affect household income of farmers is land area, length of education, KUAT and Subak role, social, economic and technical benefits. The suggest based on the findings of the study, that the intensive training required to Subak Guama members to increase knowledge about the agribusiness and can increase revenue. Motivation to younger generations as farmers urgently needed, KUAT  is expected to buy all the farmer production .
Keywords: income, farm households, gini ratio, agribusiness development